Design of Elastomeric Bridge Bearing Pad Compound Formula Based on Hydrogenated Natural Rubber - Puspitasari, Santi; Cifriadi, Adi (Journal of Engineering and Technological Sciences, 2019)
Laminated elastomeric bearing pad which is commonly produced by natural or chloroprene rubber is functioned as isolation system in bridge or flyover structures. In the research, hydrogenated natural rubber (HNR) was evaluated its feasibility to be used as base elastomer on steel-laminated bearing pad production by designing rubber compound formula. The compounding procedures of HNR applied various vulcanization system and carbon black filler types. The physical and mechanical tests result showed that only hardness parameter could fill the standar quality requirement of commercial elastomeric bearing pad as stated in AASHTO M251 in the range of 50 ? 70 Shore A scale. The tensile property and compression set value of the HNR vulcanizates were under the requirement. This was due to low rubber-filler interaction and rigidity of crosslink network. The low interaction was more evident with increasing carbon filler particle size. By adjusting semi efficient vulcanization system and used N220 as carbon filler in designing compound formula,HNR was regarded as alternative promosing base elastomer for elastomeric bridge bearing pad manufacture. Nevertheless, it was necessary to improve the procedure to achieve better tesile property and compression set parameter.